Правовий нігілізм як форма деформації правової свідомості населення - Бурдоносова, М.А. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Исследуются основные особенности общественного сознания и его уровни, определяется понятие деформации правосознания и причины этого явления. Автор рассматривает развитое правосознание как необходимое условие осознания достоинства права и основу для его практического применения в жизни, правовой нигилизм как одну из форм деформации правового сознания граждан. The article is connected with theoretical problems of public consciousness and its levels. The author analyzes such juridical term as «deformation of feeling for law and order» and its reasons. Special attention is given to the extensive interpretation of idea of legal nihilism that in the modern legal literature is not examined enough. This why the author pay attention on this term and examine legal nihilism as the form of deformation offeeling for law and order.